Evaluation of Airport Pavement Designs for Seasonal Frost and Permafrost Conditions ... - Ashtiani, Ali Z; Parsons, Timothy Tim; Applied Research Associates (Federal Aviation Administration: William J. Hughes Technical Center, 2023)
In recent years, the Federal Aviation Administration (FAA) Alaskan Region reported performance issues with some flexible airport pavements. The issues were attributed to changes in the thermal regime of the permafrost layers due to a warming trend, but the poor pavement performance could have been exacerbated or caused by factors such as improper design and construction. The FAA Airport Technology Research and Development Branch reviewed the pavement failures, design, and construction histories to determine the cause(s) and contributing factors of flexible pavement performance issues. The goal was to determine if and where modifications to FAA guidance concerning design and construction in frost and permafrost zones were needed. ...